Abordaje de la ansiedad en pacientes diagnosticados de cáncer - Muñoz Alga, María José; Bernal García, Patricia (Psicooncología, 2017)
Objective: The diagnosis of cancer can be considered as a high stressor which produce emotional reactions and emotional disorders like anxiety disorder, mood disorder or adjustment disorder. Given the high frequency of anxious symptoms in patients with diagnosis of cancer, our objective is to review the effectiveness of the psychological treatments used to approach the anxiety in cancer patients.Method: We performed a bibliographic review in PubMed database with the terms: anxiety treatment AND cancer. We analyzed scientific articles published since February 2007 to February 2016 with a sample of cancer patients.Results: We analyzed 40 articles with homogeneity in terms of diagnosis, kind of cancer and sex (most common females). 34 of them demonstrated to be effective in reduction of anxiety (the most used were mindfulness, cognitive behavioral approaches and relaxation). The complementary therapies have demonstrated variable results. Techniques like yoga were ineffective.Conclusion: There are multiple non farmacological options to reduce the anxiety in oncological patients. Most of techniques studied shown to be effectiveness in reduction of anxiety and achieve other benefits as reduction of depressive symptoms associated with a new diagnosis of cancer or associated with medical interventions.
Keywords: Anxiety; cancer; treatment; psychological approach.